Implementasi Sistem Informasi Manajemen Keuangan pada UMKM untuk Pengambilan Keputusan - Ananda Amelia; Muhammad Irwan Padli Nasution (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to explain how the implementation of a Financial Management Information System (MISK) can improve decision-making capabilities in Micro, Small, and Medium Enterprises (MSMEs). In the digital era, MSMEs are required to manage their finances quickly, accurately, and in an integrated manner to compete in a dynamic market. The SIMK offers a solution to simplify the process of recording, analyzing, and reporting financial information in real time, enabling business decisions to be based on valid data. Analysis of various studies shows that the implementation of a MISK can improve operational efficiency, financial reporting transparency, and the quality of managerial decisions. However, its effectiveness is greatly influenced by financial literacy, digital readiness, and the ability of human resources to operate the system. Many MSMEs still have not fully utilized technology due to limited capital and accounting knowledge. With training and government policy support, the implementation of a MISK is expected to strengthen the competitiveness of MSMEs, increase productivity, and achieve professional financial governance.